Pengaruh Penerapan PSAK Nomor 71 pada Kinerja Perbankan Indonesia yang Terdaftar di BEI - Fiorintari, Fiorintari; Widodo, Agus; Mahyus, Mahyus; Sari, Wida Arindya (Eksos, 2024)
This research was motivated by changes in the implementation of PSAK in the banking world, which initially used PSAK 50 and 55, then replaced with PSAK 71 to calculate the CKPN. This research aims to determine the effect of implementing PSAK 71 on CKPN on the performance of banks listed on the Indonesia Stock Exchange (BEI). This new policy standard for implementing PSAK 71 begins in 2020 and has an impact on CKPN and non-performing loans in a bank. Problematic credit can cause potential losses to banks. This research was conducted on banks in Indonesia and registered on the IDX. This study uses a quantitative approach. The data collection techniques used are documentation studies and library methods. The implementation of PSAK 71, which is proxied by CKPN, has a significant negative effect (0.010) on the profitability of banking companies with the largest assets in Indonesia which are listed on the BEI in 2019-2022. CKPN is formed in anticipation if the debtor (borrower) experiences default in the future during the loan period. The implementation of PSAK 71 requires banks to increase reserves (CKPN). This CKPN is recognized as a company expense. As the company's operational expenses increase, the company's profitability (ROA) decreases.